A Rare Presentation of Community Acquired Methicillin Resistant Staphylococcus aureus. (28th December 2013) - Docekal, J.; Hall, J.; Reese, B.; Jones, J.; Ferguson, T.
Abstract : Prostatic abscess is a rarely described condition and is commonly caused by gram-negative organisms such as enterobacteria. However, as the prevalence of methicillin resistant Staphylococcus aureus (MRSA) increases in the community, unusual infections due to this organism have been recently published. In this report, we describe a patient with diabetes mellitus type 2, who presents with diabetic ketoacidosis—later found to be due to a prostatic abscess from which MRSA was cultured.